Growth performance of different fish species during dry period in Chitwan, Nepal - Neupane, P.; Rai, S.; Kafle, H.; Ranjan, R. (Journal of Agriculture and Forestry University, 2022)
In order to assess the growth and yield of different fish species during dry period, an experiment was conducted in the Aquaculture Farm of Agriculture and Forestry University, Rampur, Chitwan from 1 April to 10 July, 2021. The experiment included three treatments: T1 (Carp polyculture), T2 (Common carp Cyprinus carpio monoculture) and T3 (Nile tilapia Oreochromis niloticus monoculture), each with three replications. Silver carp (Hypophthalmichthys molitrix 7%), Bighead carp (Aristichthys nobilis 20%), Grass carp (Ctenopharyngodon idella 13%), Rohu (Labeo rohita 30%), Mrigal (Cirrhinus mrigala 10%) and Common carp (20%) were stocked at densities of 1,400, 4,000, 2,600, 4,000, 6,000 and 2,000 fish/ha, respectively. Stocking density of Common carp and Nile tilapia was 20,000 fish/ha. Fish were fed with sinking pellet (28% crude protein) at the rate of 3% of body weight. Gross and net fish yield was significantly higher in T3 (89.89±0.67 t/ha/yr,16±0.25 t/ha/ yr) than in T2 (4.88±0.38 t/ha/yr, 4.05±0.35 t/ha/yr) due to higher (p<0.05) survival in T3 (72.5±11.3 %) than in T2 (40.6±4.5 %). Gross margin was significantly higher in T3 (1,257,482±186,600 NRs./ha/yr) than in T2 (434,250±124,753 NRs./ha/yr). Based on higher survival, yield and gross margin, Nile tilapia monoculture is suitable for dry season.